A narrative inquiry of teacher educators' professional agency, identity renegotiations, and emotional responses amid educational disruption. (December 2021) - Chaaban, Youmen; Al-Thani, Hessa; Du, Xiangyun
Abstract: Employing a narrative inquiry, the study explored the way nine teacher educators responded temporally to the emotionally-laden challenges faced during the disruption to education caused by the COVID-19 pandemic, with a focus on their enactment of professional agency and renegotiation of their identities. Findings revealed seven conflicting themes located within personal, relational, and contextual spaces. Emotional experiences were further found to direct the dynamic forms of agency enacted, and consequently the consolidation or dismissal of renegotiated identities. The study concludes with the need to support teacher educators' professional agency as a resource for transformative changes and innovations in teacher education. Highlights: Narrative inquiry revealed the dynamic nature of professional agency. A complex interplay of factors influence professional agency and identity renegotiations. Professional agency was intricately connected to professional identities. Emotional responses directed the form of agency enacted.